Предельные теоремы в критических ветвящихся процессах Гальтона - Ватсона с миграцией - Бадалбаев, И.С.; Якубов, Т.Д. (Український математичний журнал, 1995)
Розглядаються критичні гіллясті процеси Гальтона - Ватсона з міграцією. Припускається, що другий момент числа безпосередніх нащадків однієї частинки дорівнює нескінченності. Одержані граничні теореми для випадку, коли середнє міграції дорівнює нулеві. Робота узагальнює результати С. В. Нагаєва та Л. В. Хан [Teor. Veroyatn. Ee Primen.,25, No. 3, 523–534 (1980)] для скінченного другого моменту. We study critical Galton-Watson branching processes with migration. It is assumed that the second moment of the number of direct descendants is infinite. Limit theorems are proved for the case where the mean value of migration is equal to zero. The work generalizes the results obtained by Nagaev and Khan [Teor. Veroyatn. Ee Primen.,25, No. 3, 523–534 (1980)] for the case where the second moment is finite.